Digital models for the selection of party organs and election candidates in Spanish political parties: the impact of intraparty democracy - Sánchez Medero, Gema (Frontiers in Political Science, 2024)
Processes for selecting party officials and election candidates are key aspects of the internal democracy of political parties. This is not only because they reveal who is appointed, but also because they provide insight into intra-party dynamics and the levels of internal democracy within the parties. The aim of this article is to offer a general overview of the internal selection models used by Spanish political parties with representation in the Congress of Deputies, in order to determine whether online procedures are as widespread as is often believed, and, whether they have any real impact on intra-party democracy. We look into whether political parties are making widespread use of digital tools to promote new selection processes, whether the establishment of online selection mechanisms impacts the internal democracy of political parties and what types of parties are primarily using these tools. For this purpose we have conducted a taxonomy of the selection processes in Spanish political parties represented in the Congress of Deputies, based on the development of a model of indicators drawing on some previous studies.